A method of determining the quality of a base of a waterproofing membrane

CN116973196BActive Publication Date: 2026-11-03SHENZHEN ZHUOBAO TECH +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310839359.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-10
Publication Date
2026-11-03
Estimated Expiration
2043-07-10

AI Technical Summary

Technical Problem

Existing technologies lack reliable methods for testing the quality of waterproof membrane base materials. Furthermore, traditional extraction methods are time-consuming and use harmful solvents such as trichloroethylene, resulting in inaccurate test results and harm to the environment and human health.

Method used

Ultrasonic cleaning is used instead of reflux extraction. A mixed solvent of methyl tert-butyl ether, ethanol and n-hexane is used to extract the waterproof membrane base. Combined with ultrasonic extraction and drying steps, powder impurities on the surface of the base are thoroughly removed, improving the accuracy of detection.

Benefits of technology

It shortens the testing time, avoids the harm of trichloroethylene to human health and the environment, and ensures the accuracy and safety of tire base quality testing.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application provides a method for determining the quality of the tire base of waterproofing roll material, which uses a mixed solvent of methyl tert-butyl methyl ether and ethanol as an extractant, thereby avoiding the use of trichloroethylene extractant in the prior art, and further avoiding the damage to the liver, kidney, heart and nervous system of the tester caused by trichloroethylene extractant, and also avoiding the pollution to the environment such as air and water source caused by trichloroethylene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of waterproof membranes, specifically relating to a method for determining the quality of the base material of waterproof membranes. Background Technology

[0002] With the rapid development of society and the economy, infrastructure construction, especially residential and transportation infrastructure, has been developing at a rapid pace in recent years. This has led to increasingly higher requirements for building materials, particularly in terms of leak prevention, drawing continuous attention to the performance of waterproofing materials. Waterproofing materials are indispensable for protecting the safety and lifespan of basic buildings, with waterproof membranes being the most widely used. Waterproof membranes are flexible building materials that can be rolled up and used primarily in urban infrastructure such as building walls, roofs, tunnels, highways, and landfills to resist external rainwater and groundwater seepage. As a leak-proof connection between the foundation and the building, it forms the first line of defense in the entire waterproofing project, playing a crucial role in its overall success.

[0003] The quality of the waterproof membrane substrate is a crucial indicator for judging and differentiating the quality of waterproof membranes, and it is also an essential indicator in the performance testing of asphalt waterproof membranes. However, there is currently no reliable method for testing the quality of the waterproof membrane substrate. Summary of the Invention

[0004] To address the problems existing in the prior art, the inventors of this invention have conducted extensive research on existing waterproof membrane performance testing methods and have provided a method for determining the quality of the base material of waterproof membranes. This method replaces the solvent reflux extraction method, which saves testing time to a certain extent. At the same time, it does not use trichloroethylene as an extraction solvent, making the experimental process more human-friendly and environmentally friendly, and the test results are more accurate.

[0005] The technical solution of the present invention is as follows.

[0006] A method for determining the quality of the base material of a waterproof membrane includes the following steps:

[0007] S1: Cut a sample from the roll material;

[0008] S2: The sample is placed in the extractant for extraction, and then the extractant is removed to obtain the pre-extracted matrix;

[0009] S3: Repeat step S2 until the extractant turns light yellow and no powder impurities are suspended, thus obtaining the pre-purified base.

[0010] S4: Remove the residual extractant from the pre-purified carcass to obtain a fully extracted carcass;

[0011] S5: Remove the surface powder from the fully extracted carcass to obtain a purified carcass;

[0012] S6: Weigh the purified base material to obtain the mass of the waterproof membrane base material.

[0013] The current method for measuring the quality of the base material of waterproof membranes is very simple. The specific steps are as follows: cut a 100mm×100mm sample, wrap the sample in dry filter paper and tie it with thread, then place it in an extractor and heat the solvent to extract until the reflux liquid is light-colored. After that, remove the sample, let it cool and dry it, and then put it in an oven to dry. After cooling, open the filter paper package and use a brush to remove the powder on the surface of the base material. Finally, weigh the base material to obtain its quality. However, the impregnation coating of waterproof membranes has a complex composition and a very dark color. The process of heating and extracting until the reflux solvent becomes light-colored is very slow, usually taking tens of hours, which is very time-consuming. Moreover, the solvent used is usually trichloroethylene, which has an anesthetic effect on the central nervous system and can also cause damage to the liver, kidneys, heart, and trigeminal nerve. It is a carcinogen and also causes serious pollution to the air and water environment. Most importantly, after solvent extraction, the filter paper bag still contains some insoluble filler material besides the tire base. These particles are very small and easily enter the voids in the tire base. The brush cannot completely remove the powder, so the test results will be too high. This invention uses ultrasonic cleaning to replace the reflux extraction method, which saves testing time and equipment to a certain extent, and can effectively remove the powder on the surface of the tire base, thus improving the accuracy of the test results.

[0014] Preferably, in the above method, before the extraction, the method further includes removing the coating material from the sample surface. The specific steps are as follows: first, the coating material on the sample surface is melted, such as by using a hot air gun; then, the coating material on the sample surface is removed, such as by using a hot scraper to scrape off the coating material on the sample surface until no more coating material can be scraped off. There are no strict limitations on the facilities used to remove the coating material from the sample surface in this step, as long as the purpose can be achieved. The existence of this step can easily remove a large amount of coating material from the surface of the waterproof membrane, which is convenient and easy to implement, saves time for subsequent processing, and also saves the time of the entire test.

[0015] Preferably, in the above method, the extraction method in steps (S2) and (S3) is ultrasonic extraction, and more specifically, ultrasonic extraction for 15-60 minutes. The specific ultrasonic conditions are an ultrasonic frequency of 40-50 kHz and an ultrasonic temperature controlled at 45-55℃. Under these ultrasonic conditions, the stability of the ultrasonic extraction process and the extraction efficiency can be balanced.

[0016] Preferably, in the above method, the extractant used in steps (S2) and (S3) is an organic solvent, such as an organic alcohol (e.g., ethanol), a liquid saturated alkane (e.g., n-hexane), or an organic ether (e.g., methyl tert-butyl ether). The extractant of this invention replaces trichloroethylene extractant, thus avoiding harm to the environment and human health.

[0017] More preferably, in the above method, based on cost and environmental considerations, the extractant used in steps (S2) and (S3) is one or more of methyl tert-butyl ether, ethanol, and n-hexane. Most preferably, it is a mixture of methyl tert-butyl ether and ethanol in a volume ratio of 1:(0.5-5), further preferably a mixture of methyl tert-butyl ether and ethanol in a volume ratio of 1:2, or a mixture of methyl tert-butyl ether, ethanol, and n-hexane in a volume ratio of 1:(0.5-5):(0.5-1). When the waterproof membrane contains a high proportion of non-polar substances, the extractant is selected as a mixture of methyl tert-butyl ether, ethanol, and n-hexane in a volume ratio of 1:(0.5-5):(0.5-1).

[0018] The main component of waterproof membrane adhesive, asphalt, is a non-polar polycyclic aromatic hydrocarbon such as anthracene, pyrene, and phenanthrene. Gasoline and diesel fuel are higher alkanes, similar to asphalt. Based on the principle of "like dissolves like," meaning polar solutes readily dissolve in solvents composed of polar molecules, and non-polar solutes readily dissolve in solvents composed of non-polar molecules, gasoline and diesel fuel can easily and quickly dilute and dissolve asphalt. Furthermore, the methyl tert-butyl ether used in this invention is one of the main components of gasoline and diesel fuel, and similarly, based on the principle of "like dissolves like," it can quickly dilute and dissolve asphalt.

[0019] After the asphalt compound is diluted and dissolved with methyl tert-butyl ether (MTBE), a series of complex compounds are separated. These compounds can be broadly classified into water-soluble and oil-based substances. Furthermore, ethanol is hygroscopic, quickly absorbing moisture from the environment, and is miscible with water in any proportion. Therefore, the water-soluble substances obtained after dissolving the asphalt can be further dissolved in ethanol. Hexane, a straight-chain saturated aliphatic hydrocarbon, is a non-polar solvent with excellent solubility for oily substances. While the oily substances in asphalt are insoluble in both water and ethanol, they can be diluted in MTBE after dissolution. However, if individual oily substances cannot be dissolved in MTBE, hexane needs to be added to extract these specific oils, thus achieving rapid and effective extraction of the waterproof membrane components.

[0020] Preferably, in the above method, the solid-liquid ratio of the substrate to the extractant in steps (S2) and (S3) is 1:(10-20). During the extraction process, the amount of extractant used should be sufficient to completely submerge the substrate. However, the liquid level of the extractant can also be 0.5 cm, 1 cm, 1.5 cm, or 2 cm above the substrate; there are no strict limitations on this. For cost considerations, the amount of extractant used is sufficient to completely submerge the substrate.

[0021] Preferably, in the above method, the operation of steps (S2) and (S3) involves placing the extractant and the base in a sealed container to prevent the extractant from evaporating into the air during the extraction process.

[0022] In steps (S2) and (S3), the amount of extractant can be the same or different. Step (S3) is a repetition of step (S2). With repeated ultrasonic extraction and washing, the color of the extractant will gradually lighten until it becomes light yellow after 3-4 repetitions, with an approximate RGB value of (232:211:170). However, the light yellow color of the extractant does not mean that the extraction is over. Extraction needs to continue until no powder impurities are suspended in the extractant, indicating that the insoluble powder in the substrate has been washed out. In addition, when observing whether there are powder impurities suspended in the extractant, the substrate can be stirred with a glass rod or other means for 6-15 minutes before observation to ensure that the powder on the surface of the substrate is not suspended in the extractant and thus not observed. This method ensures that as many impurities as possible are removed from the substrate. Specifically, step (S3) to determine that there are no suspended impurities involves continuing extraction for 6-15 minutes after the extractant turns light yellow, while stirring the substrate and visually inspecting the extractant for any suspended impurities. If any are found, the suspending agent is replaced, and the extraction and stirring process is repeated until no suspended impurities are visually detected in the extractant. This step ensures that a large number of insoluble powder impurities in the substrate have been washed out.

[0023] Preferably, in the above method, the removal of residual extractant from the substrate after extraction in step (S4) is carried out by drying. More preferably, the drying process involves first placing the extracted substrate in air to allow the surface extractant to evaporate, then placing it in an oven at 80-120°C for 1.5-3 hours, and finally cooling the substrate to 20-30°C. More preferably, it is cooled to 20-30°C in a desiccator. In this drying step, placing the substrate in air, more precisely, in a fume hood with normal ventilation, is to prevent a large amount of extractant from being released into the indoor environment and causing health problems for laboratory personnel. When the substrate is then dried in the oven, the extractant is almost completely evaporated, having little impact on the indoor environment. If the substrate is dried directly in the oven, a large amount of extractant will rapidly diffuse into the room due to the high drying temperature, causing harm to the working environment and personnel.

[0024] Furthermore, in the above method, the specific operation of removing the surface powder of the base after removing the residual extractant in step (S5) involves tautling and vertically suspending the base after removing the residual extractant, and then removing the surface powder. In this operation, tautling and vertically suspending is only to remove as much powder as possible from the surface of the base. The removal can be done by tapping, and the degree of tautness is not strictly limited, as long as the base after removing the residual extractant is in a flat rather than curled state. In addition, there is no strict limitation on the tool for tapping the surface of the base. It can be an iron rod, a glass rod, or other rigid tool, as long as it can be used for tapping. The final degree of tapping is that no powder falls off during the tapping process. After the previous ultrasonic extraction, the process of tapping the powder will not last for a long time. Generally, tapping each side of the base about 10 times, such as 9, 10, 11, 12 times, etc., is sufficient. This step can be completed within 5 minutes.

[0025] In addition, in the above method, the instrument used to weigh the tire base in step (S6) can be any instrument capable of weighing, but based on the degree of accuracy, an analytical balance is selected for weighing.

[0026] In waterproof membranes, the base layer primarily increases the tensile strength of the membrane and allows the asphalt adhesive to adhere and form. Generally, the larger the unit area mass of the base layer of the same type, the greater the tensile strength of the waterproof membrane. Therefore, measuring the base layer mass is crucial for understanding the performance of the membrane and provides a direction for developing membranes with different properties. The method of this invention can accurately measure the base layer mass, thus providing basic research conditions for subsequent waterproof membrane development. More importantly, this invention uses a mixed solvent of methyl tert-butyl methyl ether and ethanol as the extractant, avoiding the use of trichloroethylene as the extractant in existing technologies. This avoids the damage to the liver, kidneys, heart, and nervous system caused by trichloroethylene, and also avoids the pollution of the environment such as air and water. Furthermore, the method of this invention uses ultrasonic extraction of organic soluble substances, replacing the heating reflux extraction in existing technologies, shortening the testing time. At the same time, this invention can completely remove insoluble fillers from the base layer, avoiding any impact on the accuracy of the base layer mass measurement. Detailed Implementation

[0027] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments. However, the scope of protection claimed by this invention is not limited to the embodiments.

[0028] Unless otherwise specified, all raw materials used in the following examples are commercially available. Methyl tert-butyl methyl ether, ethanol, and n-hexane were all purchased from analytical grade suppliers.

[0029] In the following embodiments, the specific step of placing the extracted substrate in the air to allow the extractant on the surface to evaporate is to place it in a fume hood under normal ventilation conditions to prevent a large amount of extractant from evaporating and entering the indoor environment. In the extraction process of the following embodiments, the solid-liquid ratio of the substrate to the extractant is 1:10.

[0030] Test Implementation Examples

[0031] Test Example 1

[0032] Cut a square sample with dimensions of 100mm × 100mm from the waterproof membrane.

[0033] Use a hot air gun to melt the coating on the surface of the roll material, and then use a hot scraper to remove the melted coating from the sample surface until the upper and lower surfaces of the substrate are exposed.

[0034] The base material with the coating removed was placed at an angle into a beaker. An extractant with a volume ratio of 1:1 of methyl tert-butyl ether and ethanol was poured in until the base material was submerged. The mouth of the beaker was then covered with an evaporating dish and placed in an ultrasonic cleaner for cleaning. After ultrasonic cleaning for 30 minutes, the extractant was removed.

[0035] Replace the mixed extractant in the beaker, sonicate again for 30 minutes, and repeat the process until the solvent turns light yellow and there are no powder impurities suspended in the extractant. When observing whether there are powder impurities suspended in the extractant, stir the base with a glass rod for 10 minutes before observing to ensure that the powder on the surface of the base cannot be suspended in the extractant and thus cannot be observed.

[0036] Remove the substrate from the beaker and place it in the air to allow the surface extractant to evaporate. Then, dry it in an oven at 105°C for 2 hours and remove it from the oven to cool to room temperature in a desiccator.

[0037] Use clamps to tighten the four corners of the tire base and hang it upright. Then, gently tap the upper and lower surfaces of the tire base with an iron rod to remove any remaining powder. Continue tapping until no powder falls off the surface of the tire base.

[0038] Weigh the material using an analytical balance. The actual mass of the waterproof membrane base is recorded as P1.

[0039] Test Example 2

[0040] Cut a square sample with dimensions of 100mm × 100mm from the waterproof membrane.

[0041] Use a hot air gun to melt the coating on the surface of the roll material, and then use a hot scraper to remove the melted coating from the sample surface until the upper and lower surfaces of the substrate are exposed.

[0042] The base material with the coating removed was placed at an angle into a beaker. An extractant with a volume ratio of 1:2 of methyl tert-butyl ether and ethanol was poured in until the base material was submerged. Then, the mouth of the beaker was covered with an evaporating dish and placed in an ultrasonic cleaner for cleaning. After ultrasonic cleaning for 30 minutes, the extractant was removed.

[0043] Replace the mixed extractant in the beaker, sonicate again for 30 minutes, and repeat the process until the solvent turns light yellow and there are no powder impurities suspended in the extractant. When observing whether there are powder impurities suspended in the extractant, stir the base with a glass rod for 10 minutes before observing to ensure that the powder on the surface of the base cannot be suspended in the extractant and thus cannot be observed.

[0044] Remove the base material from the beaker and place it in the air to allow the surface extractant to evaporate. Then, dry it in an oven at 105°C for 2 hours and remove it from the oven to cool to room temperature in a desiccator.

[0045] Use clamps to tighten the four corners of the tire base and hang it upright. Then, gently tap the upper and lower surfaces of the tire base with an iron rod to remove any remaining powder. Continue tapping until no powder falls off the surface of the tire base.

[0046] Weigh the material using an analytical balance. This is the actual mass of the waterproof membrane's base material, denoted as P2.

[0047] Test Example 3

[0048] Cut a square sample with dimensions of 100mm × 100mm from the waterproof membrane.

[0049] Use a hot air gun to melt the coating on the surface of the roll material, and then use a hot scraper to remove the melted coating from the sample surface until the upper and lower surfaces of the substrate are exposed.

[0050] The base material with the coating removed was placed at an angle into a beaker. An extractant with a volume ratio of 1:4 of methyl tert-butyl ether and ethanol was poured in until the base material was submerged. The mouth of the beaker was then covered with an evaporating dish and placed in an ultrasonic cleaner for cleaning. After ultrasonic cleaning for 30 minutes, the extractant was removed.

[0051] Replace the mixed extractant in the beaker, sonicate again for 30 minutes, and repeat the process until the solvent turns light yellow and there are no powder impurities suspended in the extractant. When observing whether there are powder impurities suspended in the extractant, stir the base with a glass rod for 10 minutes before observing to ensure that the powder on the surface of the base cannot be suspended in the extractant and thus cannot be observed.

[0052] Remove the base material from the beaker and place it in the air to allow the surface extractant to evaporate. Then, dry it in an oven at 105°C for 2 hours and remove it from the oven to cool to room temperature in a desiccator.

[0053] Use clamps to tighten the four corners of the tire base and hang it upright. Then, gently tap the upper and lower surfaces of the tire base with an iron rod to remove any remaining powder. Continue tapping until no powder falls off the surface of the tire base.

[0054] Weigh the material using an analytical balance. This is the actual mass of the waterproof membrane's base material, denoted as P3.

[0055] Test Example 4

[0056] Cut a square sample with dimensions of 100mm × 100mm from the waterproof membrane.

[0057] Use a hot air gun to melt the coating on the surface of the roll material, and then use a hot scraper to remove the melted coating from the sample surface until the upper and lower surfaces of the substrate are exposed.

[0058] The base material with the coating removed was placed at an angle into a beaker. An extractant consisting of methyl tert-butyl ether, ethanol and n-hexane in a volume ratio of 1:2:0.5 was poured in until the base material was submerged. The mouth of the beaker was then covered with an evaporating dish and placed in an ultrasonic cleaner for cleaning. After ultrasonic cleaning for 30 minutes, the extractant was removed.

[0059] Replace the mixed extractant in the beaker, sonicate again for 30 minutes, and repeat the process until the solvent turns light yellow and there are no powder impurities suspended in the extractant. When observing whether there are powder impurities suspended in the extractant, stir the base with a glass rod for 10 minutes before observing to ensure that the powder on the surface of the base cannot be suspended in the extractant and thus cannot be observed.

[0060] Remove the base material from the beaker and place it in the air to allow the surface extractant to evaporate. Then, dry it in an oven at 105°C for 2 hours and remove it from the oven to cool to room temperature in a desiccator.

[0061] Use clamps to tighten the four corners of the tire base and hang it upright. Then, gently tap the upper and lower surfaces of the tire base with an iron rod to remove any remaining powder. Continue tapping until no powder falls off the surface of the tire base.

[0062] Weigh the material using an analytical balance. This is the actual mass of the waterproof membrane's base material, denoted as P4.

[0063] Comparative Examples

[0064] Comparative Example 1

[0065] Cut a square sample with dimensions of 100mm × 100mm from the waterproof membrane.

[0066] Use a hot air gun to melt the coating on the surface of the roll material, and then use a hot scraper to remove the melted coating from the sample surface until the upper and lower surfaces of the substrate are exposed.

[0067] The base material with the coating removed was placed at an angle into a beaker. An extractant with a volume ratio of 3:1 of methyl tert-butyl methyl ether and ethanol was poured in until the base material was submerged. Then, the mouth of the beaker was covered with an evaporating dish and placed in an ultrasonic cleaner for cleaning. After ultrasonic cleaning for 30 minutes, the extractant was removed.

[0068] Replace the mixed extractant in the beaker, sonicate again for 30 minutes, and repeat the process until the solvent turns light yellow and there are no powder impurities suspended in the extractant. When observing whether there are powder impurities suspended in the extractant, stir the base with a glass rod for 10 minutes before observing to ensure that the powder on the surface of the base cannot be suspended in the extractant and thus cannot be observed.

[0069] Remove the base material from the beaker and place it in the air to allow the surface extractant to evaporate. Then, dry it in an oven at 105°C for 2 hours and remove it from the oven to cool to room temperature in a desiccator.

[0070] Use clamps to tighten the four corners of the tire base and hang it upright. Then, gently tap the upper and lower surfaces of the tire base with an iron rod to remove any remaining powder. Continue tapping until no powder falls off the surface of the tire base.

[0071] Weigh the material using an analytical balance. The actual mass of the waterproof membrane base is denoted as C1.

[0072] Comparative Example 2

[0073] Cut a square sample with dimensions of 100mm × 100mm from the waterproof membrane.

[0074] Use a hot air gun to melt the coating on the surface of the roll material, and then use a hot scraper to remove the melted coating from the sample surface until the upper and lower surfaces of the substrate are exposed.

[0075] The base material with the coating removed was placed at an angle into a beaker, and methyl tert-butyl methyl ether extractant was poured in until the base material was submerged. Then, the mouth of the beaker was covered with an evaporating dish and placed in an ultrasonic cleaner for cleaning. After ultrasonic cleaning for 30 minutes, the extractant was removed.

[0076] Replace the mixed extractant in the beaker, sonicate again for 30 minutes, and repeat the process until the solvent turns light yellow and there are no powder impurities suspended in the extractant. When observing whether there are powder impurities suspended in the extractant, stir the base with a glass rod for 10 minutes before observing to ensure that the powder on the surface of the base cannot be suspended in the extractant and thus cannot be observed.

[0077] Remove the base material from the beaker and place it in the air to allow the surface extractant to evaporate. Then, dry it in an oven at 105°C for 2 hours and remove it from the oven to cool to room temperature in a desiccator.

[0078] Use clamps to tighten the four corners of the tire base and hang it upright. Then, gently tap the upper and lower surfaces of the tire base with an iron rod to remove any remaining powder. Continue tapping until no powder falls off the surface of the tire base.

[0079] Weigh the material using an analytical balance. This is the actual mass of the base material of the waterproof membrane, denoted as C2.

[0080] Comparative Example 3

[0081] Cut a square sample with dimensions of 100mm × 100mm from the waterproof membrane.

[0082] Carefully wrap the sample with dry filter paper and tie it with thread, taking care to avoid puncturing or tearing the filter paper during the wrapping process.

[0083] Place the wrapped specimen into the extractor, add trichloroethylene to 2 / 3 of the flask's capacity, and heat to extract at 90°C to allow the extractant to evaporate and reflux.

[0084] Extract until the refluxed solvent turns pale yellow for the first time, then remove the filter paper pack, taking care to avoid tearing the filter paper during the removal process.

[0085] The removed filter paper package was left in the air to allow the extractant on the surface to evaporate, then dried in an oven at 105°C for 2 hours, and finally cooled to room temperature in a desiccator. The filter paper package was then opened on a sample sieve, and the powder on the surface of the base material inside the filter paper package was brushed off with a brush.

[0086] Weigh the base material using an analytical balance; this is the actual mass of the waterproof membrane base material, denoted as C3.

[0087] Table 1 shows the actual mass of the tire base tested in the test examples and comparative examples.

[0088] serial number Carcass weight (g) serial number Carcass weight (g) P1 3.945 C1 3.990 P2 3.878 C2 4.013 P3 3.989 C3 4.127 P4 3.856 -- --

[0089] The results in the table above show that the quality of the base material of the waterproof membrane treated by the method of the present invention is more accurate than that of commonly used methods in the prior art. The specific formulation and use of the extractant is of great significance to the method of the present invention, as it can extract the components of the waterproof membrane adhesive more effectively and obtain the quality of the base material more efficiently. In Comparative Example 3, the solvent used was trichloroethylene, the most commonly used solvent in the art. It has an anesthetic effect on the central nervous system and can also cause damage to the liver, kidneys, heart, and trigeminal nerve. It is a carcinogen and also causes serious pollution to the air and water environment. After extraction with trichloroethylene, in addition to the base material, the filter paper package also contains some insoluble filler particles. These particles are very small and easily enter the voids in the base material. The brush cannot completely remove the powder, so the test results are too high and the quality of the base material cannot be accurately obtained.

[0090] The above description is merely illustrative of preferred embodiments of the present invention and does not constitute a specific limitation on the scope of protection of the present invention. Any person skilled in the art may make changes or modifications to the techniques shown above to create equivalent embodiments. Therefore, any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention, without departing from the scope of the technical solution of the present invention, especially the content of the claims, shall still fall within the scope of the technical solution of the present invention. Furthermore, although some specific terms are used in this specification, these terms are only for convenience of explanation and do not constitute any limitation on the present invention.

Claims

1. A method for determining the quality of the base material of a waterproof membrane, characterized in that, Includes the following steps: S1: Cut a sample from the roll material; S2: The sample is placed in the extractant for extraction, and then the extractant is removed to obtain the pre-extracted matrix; S3: Repeat step S2 until the extractant turns light yellow and no powder impurities are suspended, thus obtaining the pre-purified base. S4: Remove the residual extractant from the pre-purified carcass to obtain a fully extracted carcass; S5: Remove the surface powder from the fully extracted carcass to obtain a purified carcass; S6: Weigh the purified base material to obtain the mass of the waterproof membrane base material. In steps S2 and S3, the extraction is performed by ultrasonic extraction for 15-60 minutes, with the extractant and placenta placed in a sealed container. The ultrasonic conditions are an ultrasonic frequency of 40-50 kHz and an ultrasonic temperature controlled at 45-55℃. The extractant includes a mixture of methyl tert-butyl ether and ethanol in a volume ratio of 1:(0.5-5), or a mixture of methyl tert-butyl ether, ethanol, and n-hexane in a volume ratio of 1:(0.5-5):(0.5-1). Step S3, which determines that there are no suspended impurities, involves continuing extraction for 6-15 minutes after the extractant turns a light yellow color, while simultaneously stirring the substrate. Visually inspect the extractant for any suspended impurities. If any are found, replace the extractant and repeat the extraction and stirring process until the extractant is visually free of suspended impurities.

2. The method according to claim 1, characterized in that, Prior to the extraction, the process also includes removing the coating from the sample surface, specifically through the following steps: First, the coating material on the sample surface is melted, and then the coating material on the sample surface is removed.

3. The method according to claim 1, characterized in that, The extractant consists of methyl tert-butyl methyl ether and ethanol in a volume ratio of 1:2; and / or In steps S2 and S3, the solid-liquid ratio of the matrix to the extractant is 1:(10-20) for each extraction.

4. The method according to claim 1, characterized in that, The step of removing the residual extractant in the base material in step S4 is as follows: first, place the base material in the air to allow the extractant on the surface to evaporate, then place it in an oven at a temperature of 80-120℃ to dry for 1.5-3 hours, and finally cool the base material to 20-30℃.

Citation Information

Patent Citations

  • Mesophase pitch and preparation method thereof

    CN104004536A